2019
DOI: 10.1371/journal.pone.0222833
|View full text |Cite
|
Sign up to set email alerts
|

A novel fast-slow model of diabetes progression: Insights into mechanisms of response to the interventions in the Diabetes Prevention Program

Abstract: Several models for the long-term development of T2DM already exist, focusing on the dynamics of the interaction between glycemia, insulinemia and β-cell mass. Current models consider representative (fasting or daily average) glycemia and insulinemia as characterizing the compensation state of the subject at some instant in slow time. This implies that only these representative levels can be followed through time and that the role of fast glycemic oscillations is neglected. An improved model (DPM15) for the lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 96 publications
0
22
0
Order By: Relevance
“…The study in (24) found that it was necessary to assume that the efficacy of treatment wanes with time in order to fit the data from lifestyle and drug interventions in the DPP. Here we have shown that even if the efficacy of treatment is maintained, the intrinsic dynamics of progressive beta-cell dysfunction can cause treatment to fail.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study in (24) found that it was necessary to assume that the efficacy of treatment wanes with time in order to fit the data from lifestyle and drug interventions in the DPP. Here we have shown that even if the efficacy of treatment is maintained, the intrinsic dynamics of progressive beta-cell dysfunction can cause treatment to fail.…”
Section: Resultsmentioning
confidence: 99%
“…The normal homeostatic negative feedback is converted to positive feedback, leading to deterioration in glucose tolerance and culminating in diabetes. This fundamental concept has been incorporated into other models that broadly agree but emphasize different details (23, 24, 35, 38, 43, 79). Notably, the model of (38) was shown to be able to account for the progression of fasting hyperglycemia and T2D observed in the Diabetes Prevention Program (DPP)(45).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The normal homeostatic negative feedback is converted to positive feedback, leading to deterioration in glucose tolerance and culminating in diabetes. This fundamental concept has been incorporated into other models that broadly agree but emphasize different details (23,24,35,38,43,79). Notably, the model of Ref.…”
Section: General Modeling Approachmentioning
confidence: 99%